PANDEMIC-DRIVEN BITCOIN PRICE DYNAMICS, ARTIFICIAL INTELLIGENCE PREDICTION, AND THE LOOMING QUANTUM THREAT - Yacoubian, Leandro Jorge; Ketenchian, Grigor Sahak; Garcia, Daniel Santo Padilla (Revista JRG de Estudos Acadêmicos, 2020)
This study analyzes the price dynamics of Bitcoin within the context of the COVID-19 pandemic, exploring its debated role as a safe-haven or speculative asset. The research addresses how global economic uncertainty, catalyzed by the pandemic declaration on March 11, 2020, renewed interest in decentralized crypto-assets. Furthermore, two crucial technological factors shaping Bitcoin’s future are considered: the growing application of artificial intelligence (AI) in predicting its volatile prices and the long-term threat that quantum computing poses to its cryptographic security. The methodology employed is qualitative and scenario-based, using historical price data only as a contextual baseline. Price projections are not derived from econometric models but are hypothetical estimates founded on the authors’ interpretive judgment of investor psychology, particularly the tendency of wealthy investors to accumulate assets during crises. The study projects three scenarios: in the short-term (July 2020), a price between 9,000 and 10,000; in the medium-term (end of 2020), a value of 26,629; and in the long-term (2021), a price of at least 50,000. It is concluded that while precise prediction is impossible, Bitcoin’s structural scarcity and strong speculative demand provide it with resilience. The analysis underscores that market sentiment is a key driver of its valuation.